1981
DOI: 10.1111/j.1365-2141.1981.tb07234.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin Synthesis by Fetal Erythroid Cells in an Adult Environment

Abstract: Although the developmental switch from fetal to adult haemoglobin production has been well characterized in terms of protein synthesis, very little is known about its control at the cellular level. In order to determine whether the switch is controlled by environmental factors or programmed into the haemopoietic cell population, we have studied the effects of transplantation of fetal and adult haemopoietic cells into lethally irradiated lambs on haemoglobin synthesis by the transplanted cells. In two lambs whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For example, studies of erythroid differentiation in the sheep indicate that the early fe tal HSC are committed to giving rise to fetal erythrocytes, which express iJ(2Y2 hemoglobin, whereas more mature HSC are committed to generating erythrocytes of the adult phenotype (iJ(2f32 hemoglobin) (10)(11)(12)(13). More recently, similar reconstitution studies showed that HSC in adult bone marrow fail to regenerate murine CD5+ B cells which were newly identified by multiparameter FACS analyses (14).…”
Section: Definition Of a Developmental Lineagementioning
confidence: 94%
“…For example, studies of erythroid differentiation in the sheep indicate that the early fe tal HSC are committed to giving rise to fetal erythrocytes, which express iJ(2Y2 hemoglobin, whereas more mature HSC are committed to generating erythrocytes of the adult phenotype (iJ(2f32 hemoglobin) (10)(11)(12)(13). More recently, similar reconstitution studies showed that HSC in adult bone marrow fail to regenerate murine CD5+ B cells which were newly identified by multiparameter FACS analyses (14).…”
Section: Definition Of a Developmental Lineagementioning
confidence: 94%
“…It is not controlled by the site of erythropoiesis (Wood & Weatherall, 1973) nor is it affected by severe endocrine perturbations (Wood et al, 1978). Direct approaches to the problem have included the transplantation of foetal haemopoietic cells to irradiated adult animals in an attempt to distinguish between autonomous programming of the cells and extracellular inducers (Zanjani et al, 1979;Bunch et al, 1981). After transplantation foetal cells switch to adult haemoglobin production but the time at which they do so appears to depend on their gestational age, suggesting that their pattern of haemoglobin production may be largely determined by a developmental clock intrinsic to the haemopoietic cells but perhaps capable of modulation by extracellular influences (Wood & Bunch, 1983).…”
Section: Nondeletionforms Ofd/3 Thalassaemia and Hpfhmentioning
confidence: 99%
“…It was reported that in lambs carrying the PA gene a small proportion of PC (~1 5 % of total p) appears transiently after birth and persists for several months (10). Many attempts have been made to influence the time of onset of the switch from fetal (7) to adult (P) Hb but these have been largely unsuccessful (8,9,11,12). Once commenced, the rate of the switching process has been shown to be able to be modulated.…”
mentioning
confidence: 99%